2006
DOI: 10.3122/jabfm.19.2.110
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Academic Detailing on Breast Cancer Screening among Primary Care Physicians in an Underserved Community

Abstract: Background: Urban minority groups, such as those living in northern Manhattan and the South Bronx, are generally underserved with regard to breast cancer prevention and screening practices. Primary care physicians are critical for the recommendation of mammography and clinical breast examinations to their patients.Design: Two medically underserved communities were matched and block randomized. The aim of the study was to assess the efficacy of academic detailing in increasing recommendations for breast cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 58 publications
1
33
1
Order By: Relevance
“…With regard to 83% of the female respondents willing to undergo BSE if the PHC physician advises it, is in accordance with several studies, suggesting that the primary care physicians can significantly alter the behavior of their patients with regard to regular breast examinations. [3132]…”
Section: Discussionmentioning
confidence: 99%
“…With regard to 83% of the female respondents willing to undergo BSE if the PHC physician advises it, is in accordance with several studies, suggesting that the primary care physicians can significantly alter the behavior of their patients with regard to regular breast examinations. [3132]…”
Section: Discussionmentioning
confidence: 99%
“…A group randomized implementation trial in 32 primary care practices found a 4.9% (adjusted) increase in CRC screening (colonoscopy, FS, and FOBT) and 7.9% increase in CRC screening recommendation due to an AD with audit and feedback intervention. For breast cancer screening, a randomized block study of 168 primary care physicians found that AD intervention increased recommendation for mammography and practical breast examinations in an urban community [23]. Finally, a randomized controlled trial of 16 practices found that AD with chart audit and feedback was associated with a significant increase in recommendation for and receipt of breast cancer screening in Oklahoma [24].…”
Section: Introductionmentioning
confidence: 99%
“…The fact that the intervention was effective in a population with severe cancer health disparities underscores its importance and potential to greatly effect change. The intervention was delivered using academic detailing, and while there is evidence that academic detailing can be used to increase cancer screening in urban environments (Sheinfield-Gorin et al, 2006), to our knowledge there are no reports of its effectiveness with rural populations, thus indicating the importance of the results of this current study.…”
Section: Discussionmentioning
confidence: 98%
“…Academic detailing is a highly adaptable method of education where physicians are instructed through personal contact with an individual or group focused on a specific topic (Soumerai and Avorn, 1990; Albert et al, 2004; Gorin et al, 2006). This method was selected because of the rural locations of the primary health care providers and their limited time for continuing education.…”
Section: Methodsmentioning
confidence: 99%